Classes of homogeneous financing constraints and corporate investment - Alfonsina Iona; Leone Leonida (Queen Mary University of London, School of Economics and Finance, 2024)
Does corporate finance literature accurately identify firms facing homogeneous financing constraints when studying the impact of financing constraints on corporate investment? The short answer is no. The common practice of using pre-determined percentiles of a financing constraint metric compromises the validity of conclusions. Our empirical framework identifies four classes of firms facing homogenous financing constraints independently of the financing constraints metric used. Moreover, we show that while popular metrics of financing constraints may capture financing constraints reasonably well, differently from previous studies the sensitivity of investment to cash flow is inverse basin-shaped. We provide an understanding of this shape by studying investment and financial policies jointly, under different regimes of financing constraints.
Keywords: C13; D25; G30; G31; G32; 330; Homogeneous Financing constraints; Sorting scheme; Inverse basin shaped investment-cash flow sensitivity; Interdependence of financial policies